Late summer habitat selection by breeding waterfowl in northern Scotland - Fox, A D; Jarrett, N; Gitay, H; Paynter, D (Wildfowl, 1989)
The majority of lochs and water courses were visited in an area of northern Scotland during July 1988. The breeding waterfowl of these waters were recorded along with details of environmental parameters at each site, including water quality. In a correspondence analysis, three axes accounted for 72% of the variance, with conductivity, pH and other measures of habitat type all highly represented. Site analysis showed that different species had distinct habitat preferences. Waterfowl of most restricted distribution on the peatlands (namely Black-throated Diver and Common Scoter) showed strong preferences for lochs with islands and with high pH/conductivity, Red-throated Divers tended to occur on mid-range water quality lochs, Teal selected acidic, base-poor waters and Mallard showed little selectivity in their use of peatland waters. Some implications of peatland afforestation are discussed with respect to breeding waterfowl communities.